2021
DOI: 10.1186/s12905-021-01345-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the association of cognitive abilities and emotional function with allergic disorders in young women

Abstract: Background Allergic disorders may have a bidirectional causal relationship with mental disorders. In this cross-sectional study, we aimed to assess the associations between cognitive abilities and emotional function tests and quality of life with the presence of allergic disease in young women. Methods A diagnosis of allergic disorders, comprising allergic rhinitis (AR), asthma and atopic dermatitis (AD), was confirmed by a specialist in allergy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…One of the eight studies [ 29 ] found no significant difference between the atopic dermatitis group and the healthy group in terms of tasks related to cognitive abilities. However, it was shown that people with atopic dermatitis had higher scores on the depression and stress scale.…”
Section: Resultsmentioning
confidence: 99%
“…One of the eight studies [ 29 ] found no significant difference between the atopic dermatitis group and the healthy group in terms of tasks related to cognitive abilities. However, it was shown that people with atopic dermatitis had higher scores on the depression and stress scale.…”
Section: Resultsmentioning
confidence: 99%
“…The most common symptoms of ARC are runny nose, congestion, sneezing, and itchy, watery eyes. At times, the symptoms of ARC can be severe, disrupting sleep, interfering with the ability to perform daily activities, and inducing anxiety, irritability, fatigue, and frustration (1)(2)(3)(4). The symptoms of ARC can even impair cognitive function and affect school performance (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite there are many studies that showed the association between ADHD and allergic diseases and explained it genetically and physiologically, the number of studies that focused on ADHD-related cognitive dysfunctions was relatively small and showed inconsistent results. For example, some studies have reported that dysfunctions in concentration, selective attention, and psychomotor speed were related to AR [6-8], but con icting results also existed [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%